The Effect of E-Service Quality and Ease of Use on Customer Satisfaction of Digital Customer Service Machine Users at PT Bank Central Asia, Tbk KCP A. Rivai - Chandra, Fika; Widiyanti, Marlina; Wahab, Zakaria; Maulana, Ahmad (Politeknik Siber Cerdika Internasional, 2025)
This study was conducted with the aim of determining the influence of e-service quality and ease of use on customer satisfaction of digital customer service machine users at PT Bank Central Asia, Tbk KCP A. Rivai. The population in this study is all customers who use Digital customer service machines at PT Bank Central Asia, Tbk KCP A Rivai as many as 4,703. The sample used in this study was 151 respondents using the slovin formula. The results of multiple linear regression analysis show that e-service quality and ease of use have a positive and significant effect on customer satisfaction. E-Service Quality, PT Bank Central Asia, Tbk is expected to maintain digital cs services from the current contact side because it is able to provide satisfaction to Bank BCA customers. However, the BCA indicator provides several options to contact the call center (Halo BCA) (Telephone, WA, email) with a value below average. Ease of Use, is expected to be able to check the digital cs machine before starting the service. In addition, it is also necessary to carry out regular maintenance to avoid damage when the digital cs machine is used.